Analisis Adopsi Uang Elektronik dengan Model UTAUT2 - Cahyani, Ni Putu Diva; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi, 2022)
This study aims to explain the intention and behavior of using electronic money using the UTAUT2 model. This research was conducted in Badung Regency. The sampling method used is accidental sampling. The data collection method is carried out by distributing online and paper-based questionnaires to the people of Badung Regency who use electronic money that has been registered with Bank Indonesia. The total sample is 252 people. The data analysis technique used SEM-PLS. The results of this study indicate that socio-cultural factors, facilitating conditions, price values, and habits have a significant positive effect on the intention to use electronic money, meanwhile, performance expectations, business expectations and hedonic motivation have no effect on intentions to use electronic money. In addition, the facilitating conditions, habits, and usage intentions have a positive and significant effect on the behavior of using electronic money. Keywords: Behavior Intention of Electronic Money; Use Behavior of Electronic Money; UTAUT2